The structure and phase composition of the U9 steel surface layer alloyed with chromium atoms under the action of compression plasma flows - Cherenda, Nikolai N.; Malashevich, Alexander A.; Uglov, Vladimir V.; Astashynski, Valentin M.; Kuzmitski, Anton M. (Journal of the Belarusian State University. Physics, 2017)
In this work, the elemental and phase compositions as well as mechanical properties of the instrumental U9 steel surface layer alloyed with chromium atoms under the action of compression plasma flows, generated by the magnetoplasma compressor of compact geometry, were investigated. X-ray diffraction analysis, scanning electron microscopy, energy dispersion microanalysis, and microhardness measurements were used to study the modified layer structure and properties. The findings show that an increase of the energy density absorbed by the surface leads to growth of the alloyed layer thickness and to the increased surface erosion intensity and hence results in a decrease of the chromium concentration in this layer. X-ray diffraction analysis reveals the presence of the metastable γ-Fe phase in the alloyed layer. Existence of the metastable phase can be explained by its stabilization with the nitrogen atoms diffused from the residual atmosphere of the vacuum chamber. The concentration of this phase is depending on the treatment parameters. The formation of the surface layer dispersed structure leads to increase of the microhardness by a factor of two and more.
Keywords: compression plasma flows; structural and phase changes; alloying; instrumental steel